EXPRESSIVE SPEECH ACTS IN DHARMANN’S SERIAL - Rawindra Sufix Diwyacitta; Yuli Widiana (Humaniora Scientia, 2024)
Comprehending the theory of speech acts is very important in communication because everyone needs to understand each other. Communication might involve a lot of interactions containing expressive speech acts, especially in the entertainment world. This research aims to identify the types of expressive speech acts and to describe the function of each type of expressive speech act in DharMann’s serial show on YouTube. This research is classified as qualitative descriptive research. The data of this research were utterances that contain expressive speech acts found in the DharMann’s channel videos. Collecting data was collected by transcribing the English subtitles of DharMann’s videos, classifying the type of expressive speech acts, and the last is coding the data. Furthermore, the data analysis technique was based on Kreidler’s (2013) classification of expressive speech acts. The collected data were classified based on the types of expressive speech acts. After that, the functions of each type were described based on the pragmatics contexts. The result described the five types of expressive speech acts used by the characters from DharMann’s videos, such as attitude, apologizing, praising, thanking, and congratulating. Attitude functions to make the interlocutor understand what the speakers feel. Apologizing functions as a form of self-acceptance for a mistake that has been made. Furthermore, praising functions to make the person being praised feel comfortable and happy while thanking functions to show gratitude and respond to statements made by the speaker. Then, congratulation functions as a form of appreciation for someone's achievement. The most dominant type of expressive speech act was attitude. This fact strengthens the theory which states that expressive speech acts are used to express feelings related to psychological conditions. Congratulating is rarely found because the contexts related to one’s achievement are limited. Through expressive speech acts, the speaker's sincerity is conveyed so that the listener can believe in what the speaker has said. In general, expressive speech acts are used on the serial show to trigger viewers’ emotions as a part of entertainment.